PERENCANAAN DAN PENGEMBANGAN PROGRAM STUDI MANAJEMEN ZAKAT DAN WAKAF FAKULTAS EKONOMI DAN BISNIS ISLAM IAIN BENGKULU BERBASIS PENGGUNA LULUSAN - Nurul Hak; Yenti Sumarni (Universitas Darussalam Gontor, 2022)
IAIN Bengkulu consists of four faculties. One of them is the Faculty of Economics and Islamic Business (FEBI). FEBI IAIN Bengkulu has a very small department and the only one in Bengkulu Province it has is the Zakat and Waqf Management study program. Of the 4 study programs at FEBI IAIN Bengkulu, only this study program has little interest. The purpose of this study is to explain the learning outcomes of graduates in the curriculum of the Zakat and Waqf Management Study Program. To Explain How SWOT Analysis Against CPL Zakat and Waqf Management Study Program. To Explain How the Planning and Development Strategy of Zakat and Waqf Management Study Program. This type of research is qualitative with research methods to find naturalistics carried out in natural conditions where the object develops as it is, research is not imitated and the existence of research on object dynamics is not influenced. So whatever is found in the field does not improve the data. That data is analyzed and then written in the research report. The results of the research are the Learning Outcomes of Graduates in the Zakat and Waqf Management Study Program Curriculum According to Users The graduates of the curriculum in the Zakat and Waqf Management study program have met the standards and some are in accordance with graduate users and some knowledge that needs to be adapted to graduate users including IT-based knowledge and applications, deepened Religious knowledge, especially Tahfis and about the ethics of a charity. SWOT Analysis of the CPL of Zakat and Waqf Management Study Program Graduates Based on Users Strategy is a comprehensive plan that integrates all resources and capabilities that have a long-term goal to achieve an expected goal. The Study Program can move quickly and correctly, when there is the ability to determine a new position with a new paradigm and orientation which is also called repositioning. The repositioning of the study program is carried out by assessing and reviewing the results of the SWOT analysis of the research results above from all strengths, weaknesses, opportunities and threats so that it can determine which ones must be improved and which ones must be strengthened according to the themes and components. Among the MAZAWA study program development strategies that will be implemented include preparing short, medium and long term strategic plans. The short-term strategic plans of the MAZAWA study program include evaluating the development draft of the Merdeka Learning curriculum for the Merdeka Campus